1938
DOI: 10.1111/j.1467-6494.1938.tb02276.x
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Measurement of Individual Differences in Personality*

Abstract: This Study outlines an approach to the measurement of individual differences in personality. The approach was suggested by a gross observational comparison of mental hospital patients and college students. This comparison was refined by means of an original method of scaling and scoring the answers given to psychological inventories. HISTORICAL REVIEWThe Investigation of Individual Differences Individual differences in various aspects of behavior were first noted by gross observational comparison of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1941
1941
1954
1954

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Some of the problems indicated herein are reported on more fully in subsequent papers. 2 Appreciation is expressed to the Research Board of the University of Illinois for financial aid in support of this study, and to Mr. Russell J. Jessen and Mrs. Gail Pheney Jessen, Research Assistants. II8 logical characteristics of items which are found to differ from one another empirically in their effectiveness in measuring personality integration.…”
Section: ''~E Problemmentioning
confidence: 98%
See 4 more Smart Citations
“…Some of the problems indicated herein are reported on more fully in subsequent papers. 2 Appreciation is expressed to the Research Board of the University of Illinois for financial aid in support of this study, and to Mr. Russell J. Jessen and Mrs. Gail Pheney Jessen, Research Assistants. II8 logical characteristics of items which are found to differ from one another empirically in their effectiveness in measuring personality integration.…”
Section: ''~E Problemmentioning
confidence: 98%
“…Before outlining differences in results deriving from these three groups of item pairs, it is helpful to discuss various differences in our scoring methods. In our previous studies (2,4,7), and in the item analysis of the present study, we included two scoring steps which were omitted in all other portions of this study. They were omitted even though a previous study (2) had found that one of these steps increased the correlation between two tests of the variable under consideration, and also increased the difference between group means of patients and a group of normals.…”
Section: I20mentioning
confidence: 99%
See 3 more Smart Citations